Using Data Sonification to Overcome Science Literacy, Numeracy, and Visualization Barriers in Science Communication - Sawe, Nik; Chafe, Chris; Treviño, Jeffrey (Frontiers in Communication, 2020)
Sharing the complex narratives within scientific data in an intuitive fashion has proven difficult, especially for communicators endeavoring to reach a wide audience comprised of individuals with differing levels of scientific knowledge and mathematical ability. We discuss the application of data sonification – the process of translating data into sound, sometimes in a musical context– as a method of overcoming barriers to science communication. Data sonification can convey large datasets with many dimensions in an efficient and engaging way that reduces scientific literacy and numeracy barriers to understanding the underlying scientific data. This method is particularly beneficial for its ability to portray scientific data to those with visual impairments, who are often unable to engage with traditional data visualizations. We explore the applications of data sonification for science communicators and researchers alike, as well as considerations for making sonified data accessible and engaging to broad audiences with diverse levels of expertise.